PENGARUH INDEKS PEMBANGUNAN MANUSIA, PERSENTASE PENDUDUK, DAN TINGKAT PENGANGGURAN TERHADAP KEMISKINAN DI PROVINSI PAPUA - Florencia, Elisa; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022, 2022)
The problem that has yet to be addressed, both nationally and regionally, is poverty. The emergence of poverty is certainly influenced by several factors including uncontrolled population growth, high unemployment, low Human Resources (HR), and Natural Resources (NR) that are not utilized properly and correctly. The purpose of this study is to analyze the simultaneous and partial effect of the Human Development Index (HDI), the percentage of the population, and the unemployment rate on poverty in the Regency/City of Papua Province. This study uses secondary data with panel data analysis method consisting of cross section data and time series data for districts/cities in Papua Province with a total of 145 research data. Research with fixed effect model shows that simultaneously HDI, percentage of population, and unemployment rate have an effect on poverty in the Regency/City of Papua Province. Partially HDI has a negative and significant effect on poverty, the percentage of the population has a positive and significant effect on poverty, and the unemployment rate has a positive and significant effect on poverty in Papua Province.